The effect of Zingiber Officinale in the treatment of ulcerative colitis (Research, Society and Development, 2023)
Ulcerative colitis is an inflammatory bowel disease, which is characterized by rectal bleeding, abdominal pain, fever, weight loss and diarrhea, is a chronic disease and tends to be progressive, drastically affecting the population's quality of life. It’s conventional treatment consists on the administration of oral or topical aminosalicylates and also corticotherapy, where it’s main objective is symptom control, nutritional balance and improvement of the patient's quality of life, and despite being efficient, it is very expensive and also has multiple side effects, that end up decreasing adherence to treatment. From this, the purpose of this narrative review is to evaluate previous studies on the properties of Zingiber officinale, which are widely known for their anti-inflammatory and antioxidant capacity, and also to analyze studies that used ginger for the treatment of ulcerative colitis, it’s epidemiological aspects and it’s conventional treatment. Despite limited but growing literature exploring the use of ginger in the treatment of ulcerative colitis, good results were presented and further research using this plant is necessary.